Genome sequence and description of Anaerosalibacter massiliensis sp. nov. (March 2016) - Dione, N.; Sankar, S.A.; Lagier, J.-C.; Khelaifia, S.; Michele, C.; Armstrong, N.; Richez, M.; Abrahão, J.; Raoult, D.; Fournier, P.-E.
Abstract: Anaerosalibacter massiliensis sp. nov. strain ND1 T (= CSUR P762 = DSM 27308) is the type strain of A. massiliensis sp. nov., a new species within the genus Anaerosalibacter. This strain, the genome of which is described here, was isolated from the faecal flora of a 49-year-old healthy Brazilian man. Anaerosalibacter massiliensis is a Gram-positive, obligate anaerobic rod and member of the family Clostridiaceae. With the complete genome sequence and annotation, we describe here the features of this organism. The 3 197 911 bp long genome (one chromosome but no plasmid) contains 3271 protein-coding and 62 RNA genes, including six rRNA genes.